Green Open Space Management in Bone Regency - Asriadi Asriadi; Muliana Muliana; Feby Triadi; Muhammad Luthfi Siraj; M. Awaluddin (Jurnal Ad'ministrare, 2020)
Green open space is one of the problems that must be considered and considered together at this time, where the condition of this area is increasingly displaced by urban areas. This study aims to analyze the management of green open space in Bone Regency with the hope that the results of the analysis can be a reference for revising the spatial plan that has been implemented but is not on target. The stages of the research method, starting from theoretical studies and empirical studies, preparation of proposals, testing the validity and reliability, data collection, analysis, and discussion. From a government perspective that sees green open space from the side to beautify urban spaces with various aesthetic touches in green open space settings. In-depth studies of environmental impacts and in-depth socio-cultural aspects carried out by the private sector have a more favorable effect on the development of green open spaces in Bone Regency. From the perspective of the community itself, who want green open space to be used for a variety of activities that can be carried out, for example by carrying out microeconomic development in areas that are built